Knowledge and use of edible and medicinal plants in two populations from the Chaco forest, Córdoba province, Argentina - Arias Toledo, Barbara (2007)
We analyze and compare plant knowledge and uses of medicinal and edible plants of two rural communities located in different phytogeographic regions. We hypothesize that there are differences in the number of edible and medicinal plants that people know and use between these communities because of environmental constraints. In addition, because of cultural erosion, we expect to find (a) a higher number of plants that people know as useful in comparison with the number of plants they actually use, and (b) a decrease in the number of useful plants cited when comparing male/female and younger/older categories. Results show a higher range of knowledge of medicinal plants than edible plants, and medicinal use included mainly those used to treat digestive problems. Based on statistical analyses, we present comparisons between the communities, age groups, and genders, and discuss how differences in these regions (e.g., geographic, ecological, cultural, etc.) may explain of the variation in the knowledge on wild useful plants between the communities.